2015
DOI: 10.1021/acs.langmuir.5b00560
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Caffeic Acid Degradation by Carbon-Doped Titanium Dioxide

Abstract: The removal of the phenolic compound, caffeic acid, by photodegradation has been investigated using carbon-doped titanium dioxide particles as a photocatalyst under visible light. UV-vis absorption spectroscopy and gas chromatography-ion trap mass spectrometry analyses revealed a substrate concentration dependence of the removal of caffeic acid from a water solution. The k2 and t(0.5) parameters of each reaction were calculated by fitting kinetics data to a second-order kinetic adsorption model. To evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…Doping of non-metal elements (e.g., C, N, S, etc.) on mesoporous TiO 2 can widen its valence band and narrow the bandgap so that the surface is more likely to generate highly active electrons and holes, which makes the photocatalysis more effective [ 53 , 54 , 55 , 56 , 57 , 58 ]. During the doping process, the non-metal anions will replace the lattice oxygen anions in TiO 2 and present as isolated atoms.…”
Section: Synthesismentioning
confidence: 99%
“…Doping of non-metal elements (e.g., C, N, S, etc.) on mesoporous TiO 2 can widen its valence band and narrow the bandgap so that the surface is more likely to generate highly active electrons and holes, which makes the photocatalysis more effective [ 53 , 54 , 55 , 56 , 57 , 58 ]. During the doping process, the non-metal anions will replace the lattice oxygen anions in TiO 2 and present as isolated atoms.…”
Section: Synthesismentioning
confidence: 99%
“…As shown in Figure 8a, in the blank test (i.e., without addition of the photocatalysts), AR18 exhibited negligible self-decomposition, revealing great stability of the dye in the process. It is known that various processes can be involved in dye solution decolorization [55,56], therefore adsorption of AR18 on CS/GCN in darkness was also performed (Figure 8c). The results revealed that adsorption equilibrium for CS/GCN was achieved after 1 h. Moreover, the lowest adsorption capacity was demonstrated by the bulk GCN (~3%).…”
Section: Resultsmentioning
confidence: 99%
“…However, their high price inhibits the particle's applications. Researchers hope to find some non-noble metals to replace novel metals [56][57][58]. Zhang et al [59] reported the synthesis of Mo-decorated TiO 2 /CNTs (Mo-CT) composites.…”
Section: D/0dmentioning
confidence: 99%